PENERAPAN MODEL PEMBELAJARAN KREATIF UNTUKMENINGKATKAN KETERAMPILAN MEMBUAT BENDAKONSTRUKSI PADA SISWA KELAS IVSD NEGERI 153 PEKANBARU - Rahmadania Rahmadania; Zariul Antosa; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThe problem of this study is the lack of students skill in making construction objects . It is because the students are not given opportunities to pour their own ideas into a work and their are not able to develop their work . Other factors derives from teachers , such as teacher -centered learning , teachers do not give enought guidance to the and students just give assignments according to the exemplies . This research was collaborative action research (CAR ) . Subjects in this study were fourth grade students with 36 students . The research instrument consisted of observations sheets of teachers and student activities , process on sheets and outcomes assessment sheets and assessment sheets of construction skills in making objects . This research was conducted in three cycles , each cycle consisted of two meetings . The results of this study , the initial data in the first was 50.61 and increased into 52.70 in the second cycle and was 68.33 and also increased into 80.69 . In teacher activity also increased in the first cycle from 58.3 to 79.1 and the score in the third cycle was 87.5 . At the student activity also increased from 54.1 % in the first cycle into 75 % and the third cycle was 83.3 % . The results of this study indicates that the application of creative learning model can improve the skills of making construction objects of the fourth grade students in SD Negeri 153 Pekanbaru.Keyword : Creative Learning Model, Creating Construction Objects Skills